Réponses

2014-09-15T19:16:36+02:00
A) f(2)=-3(2-1)²     =-3*1     =-3 
b) f(-3)=-3(-3-1)²          =-3(-4)²          =-3*16          -48 
c) -3(x-1)²=4<=> -3(x²+1)=4<=> -3x²-3=4<=>-3x²=7<=>x²=-7/3 soit x=V-7/3 => or le nombre sous la racine ne peut être négatif donc c'est impossible. 
Donc  4 n'admet pas d'antécédents par f.
d) -3(x-1)²=0<=> -3(x²+1)=0<=> -3x²-3=0<=>-3x²=3<=>x²=-1 => idem 
e) -3(x-1)²=-12<=> -3(x²+1)=-12<=> -3x²-3=-12<=>-3x²=-15<=>x²=15 D'où x=v15 ou -V15 

Source : http://nosdevoirs.fr/devoir/8330